Acute Effects of Neutrophil-Derived Oxidative Stress on Pulmonary Microvasculature - Hammerschmidt, Stefan; Gessner, Christian; Wirtz, Hubert; Wahn, Hans (Current Respiratory Medicine Reviews, 2006)
Neutrophils play a crucial role in acute lung injury as well as of chronic pulmonary diseases, e.g. pulmonary fibrosis or COPD. The sticking of neutrophils in the pulmonary microvasculature is regarded as an initial event of acute lung injury. Activated neutrophils may affect the surrounding tissue via several pathogenic mechanisms, including the release of proteolytic lysosomal enzymes, the generation of prostanoids and the production of oxidants. The activation of neutrophils includes stimulation of the membrane associated enzyme NADPH oxidase, which generates superoxide anion radical. Superoxide anion radical dismutates to form H2O2. The neutrophil-released heme enzyme myeloperoxidase catalyzes the formation of hypochlorous acid, which is a powerful neutrophil-derived oxidant. This review summarizes the action of hypochlorous acid on the pulmonary microvasculature. It compares the effects of this oxidant with the effects of stimulated neutrophils. The hypochlorous acid-induced effects on pulmonary artery pressure and on pulmonary vascular permeability are discussed together with the effects of this oxidant on biochemical parameters of oxidative stress (tissue GSH content and accumulation of lipid peroxidation products) and effects of this oxidant on pulmonary concentration of energy rich phosphates (ATP). Additionally, data on the relation between oxidative stress and pulmonary eicosanoid metabolism are discussed.
Keywords: acute lung injury